Effects of moss restoration on surface runoff and initial soil erosion in a temperate vineyard - C. Gall; S. Oldenburg; M. Nebel; T. Scholten; S. Seitz (SOIL)
Soil erosion threatens soil fertility and food security worldwide, with agriculture being both a cause and a victim. Vineyards are particularly at risk due to the often steep slopes and detrimental management practices such as fallow interlines and bare soil under the vines. Therefore, the search for alternative management practices becomes vital, and vegetation covers, including mosses, have the potential to reduce soil erosion. However, research on moss restoration as an erosion control method is still in its infancy, and this form of erosion control has never been applied in vineyards. It is thus unclear whether moss restoration can be implemented in vineyards. In this study, the restoration of mosses was investigated by applying artificially cultivated moss mats in a temperate vineyard. The effects of moss restoration on surface runoff and sediment discharge were examined compared to bare soil and cover crops using rainfall simulation experiments (45 mm h−1 for 30 min) with small-scale runoff plots at three measurement times during 1 year (April, June, and October).